Implementation of Internet of things in a mobile Humanoid robot: A base for future of IOT enabled robotics applications - Jalamkar, D; ., Krishnakumar; Selvakumar A, Arockia (International Journal of Engineering and Technology, 2018)
Â Internet of Things (IoT) is the most growing and trending technology recently in the field of mechatronics engineering. Main reason behind the growth of this technology is that it can be implemented to almost everything and everywhere. Internet of things has pretty much evolved from the â€œNext big thingâ€ to the â€œbiggest thingâ€ happening around us right now. In this paper, a complete analysis is provided to understand the amalgamation of robotics and internet of things. Robotics and Internet of things are two big fields where successive research is happening. The integration of these two would make the monitoring, implementation way better. Hence keeping this in mind, a complete analysis is made, with the hardware, software, platforms available also taken into consideration. Also other factors such as simplicity, cost, and ease of development are taken into consideration.Â Â